Nghiên cứu chế tạo màng chuyển hóa ánh sáng polyetylen có chứa chất nhị phân Eu, Y: (phen)2Eu1-xYx(NO3)3 - Thuận, Lê Bá; Liên, Đỗ Ngọc; Vượng, Nguyễn Đức; Hùng, Nguyễn Trọng; Đĩnh, Lưu Xuân (Vietnam Journal of Chemistry, 2014)
Eu-coordination compounds doped PE plastic has ability to convert light from violet into red increasing photosynthesis of plants. In this work, bis(1,10-phenanthroline)Eu(III) nitrate complex is selected as a light converter for preparation of Eu doped PE plastic film. Bis(1,10-phenanthroline)Eu(III) nitrate complex was synthesized and characterized by various physical methods such as thermal analysis, IR spectroscopy, 1H-NMR and 13C -MNR and mass spectrum. The Eu doped PE plastic film was prepared by dry mixing PE grains and powder of the complex. The optical properties of the film were characterized by absorption and emission spectra showed that the film converts light from violet into red range